Extracellular vesicles for abdominal aortic aneurysm: mechanisms, therapeutic potential, and translational challenges - Huibo Ma; Zongyou Xie; Yihang Cai; Fangda Li; Jianqiang Wu; Yuehong Zheng (Experimental Biology and Medicine, 2026)
Abdominal aortic aneurysm (AAA) is a progressive and potentially fatal vascular disease for which no effective pharmacological therapy is currently available. While surgical repair remains the only definitive treatment for advanced aneurysms, patients with small AAAs are mainly managed by surveillance, highlighting the need for disease-modifying strategies. Extracellular vesicles (EVs) have emerged as promising cell-free therapeutic tools because of their biocompatibility, ability to transfer bioactive cargo, and capacity to regulate multiple pathological processes involved in AAA progression. This review summarizes recent advances in EV-based therapies for AAA, focusing on mesenchymal stromal cell-derived EVs, immune cell-derived EVs, and engineered EV platforms. Preclinical studies suggest that therapeutic EVs can attenuate aneurysm formation by suppressing macrophage-driven inflammation, regulating macrophage polarization, inhibiting neutrophil extracellular trap-associated injury, protecting vascular smooth muscle cells from senescence, ferroptosis, apoptosis, and mitochondrial dysfunction, and limiting extracellular matrix degradation. Engineered EVs, including cargo-enriched, peptide-targeted, magnetically guided, chemotaxis-enabled, and biomaterial-assisted systems, may further improve lesion targeting, vascular retention, and therapeutic potency. However, EV-based AAA therapy remains at an early preclinical stage. Key barriers include unclear biodistribution and clearance, insufficient evidence of lesion-specific target engagement, heterogeneous EV isolation and characterization methods, uncertain dosing strategies, and the need for standardized potency, safety, manufacturing, and regulatory frameworks. Overall, EVs offer a biologically rational platform for non-surgical AAA therapy, but clinical translation requires rigorous standardization and robust evidence linking EV delivery to vascular repair.